Subject marking interrupted: Perturbations from the development of Northern Mao’s future tense suffix - Michael Ahland (Studies in African Linguistics, 2014)
Northern Mao, an Omotic-Mao language of Ethiopia, exhibits three partially overlapping but distinct subject-marking paradigms in its verbal system: subject prefixes on realis verbs which correspond closely to free pronouns, subject suffixes on irrealis negative non-future verbs which exhibit regular changes from the realis prefixes, and a third, more divergent, subject suffix system on irrealis future verbs which exhibits an [m] form not attested as a person marker elsewhere in the language or extended family. It is argued (from internal evidence) that the irrealis future verbs developed from a periphrastic subordinate + final verb complexes and that the intrusive [m] was, at an earlier stage, part of a subordinating morpheme.